The Relationship Between Outbound Activities And Formation Leadership Character For Students In Elementary School, Junior High School, And Senior High School: Literature Review - Rochma, Ana Vida Nur; Ni’maturrohmah, Mufaizin; Farhah’Izzati, Nur Amalina; Putri, Risma Verani Arfina; Fanani, Erianto (Tarqabin Nusantara Group, 2023)
Leadership character is an important thing that should exist in an individual because in determining the success of a group or organization requires a leader who has a leadership spirit in order to achieve a goal properly. The formation of this character should be done as early as possible, especially for children at school. One way to improve leadership character is through outbound activities which are often carried out in schools and can function as a medium for complex life simulations. In accordance with this statement, this review article aims to determine the relationship and influence between outbound activities and the formation of leadership character for elementary, junior high and high school students. To achieve this goal, a research method was carried out in the form of a review article using five literatures originating from an online database with a range from 20017 to 2023. The results of these articles reviewed show that outbound games are suitable and effective in improving children’s leadership characteristics at various levels of education such as increasing self confidence, courage to socialize and communicate in front of many people.